2018
DOI: 10.1177/0081246318805267
|View full text |Cite
|
Sign up to set email alerts
|

The role of family structure and parenting in first year university adjustment

Abstract: The first year of university creates new experiences and challenges for first years and lays the foundation for the subsequent years of study. This first year has implications for academic development, mental health, and well-being of students and subsequently student retention. The majority of South African university students stay within their familial home unlike their international counterparts. The family may therefore play a contributory role in adjustment to university but this role is somewhat unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In addition, motivation variables, i.e., autonomous motivation (Miquelon et al, 2005 ; Bailey and Phillips, 2015 ; Willems et al, 2021 ), self-oriented perfectionism (Miquelon et al, 2005 ), self-efficacy, and learning strategies (Willems et al, 2021 ), as well as basic psychological needs satisfaction were also found to be associated with students' academic adjustment (Carr et al, 2013 ; Vergara-Morales and Del Valle, 2021 ). In terms of family factors, parental autonomy support (Daniels et al, 2019 ), parental involvement (Smojver-Ajic et al, 2015 ), and attachment styles were significantly linked to attachment security (positive relationship with the insecurity dimension) (Carr et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, motivation variables, i.e., autonomous motivation (Miquelon et al, 2005 ; Bailey and Phillips, 2015 ; Willems et al, 2021 ), self-oriented perfectionism (Miquelon et al, 2005 ), self-efficacy, and learning strategies (Willems et al, 2021 ), as well as basic psychological needs satisfaction were also found to be associated with students' academic adjustment (Carr et al, 2013 ; Vergara-Morales and Del Valle, 2021 ). In terms of family factors, parental autonomy support (Daniels et al, 2019 ), parental involvement (Smojver-Ajic et al, 2015 ), and attachment styles were significantly linked to attachment security (positive relationship with the insecurity dimension) (Carr et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies reviewed, eight of these used a longitudinal design (Fernández et al, 2017;Heffer & Willoughby, 2017;Holt, 2014;Lindell et al, 2020;Meng et al, 2014;Nightingale et al, 2013;Park et al, 2011;Ranney & Troop-Gordon, 2012), and ten studies applied cross-sectional design (Bishop et al, 2019;Chevrier et al, 2020;Daniels et al, 2018;Katz & Somers, 2015;Lau et al, 2018;Morton et al, 2013;Nguyen et al, 2019;Rahat & ˙Ilhan, 2016;Rodrıguez et al, 2017;van Rooij et al, 2017).…”
Section: Types Of Studiesmentioning
confidence: 99%
“…To date, studies on college adjustment among first-year undergraduates are able to describe the adjustment process during the first year of college. Ten studies applied theoretical frameworks such as Attachment Theory (Bishop et al, 2019;Lindell et al, 2020), Self-determination Theory (Daniels et al, 2018;Nguyen et al, 2019), The transactional theory of coping (Heffer & Willoughby, 2017), Theory of Emerging Adulthood (Lindell et al, 2020); Self-efficacy (Meng et al, 2014), Social Compensation Theories (Ranney & Troop-Gordon, 2012), Tinto's Student Departure Theory (Rodrıguez et al, 2017), Tinto's Theory of Student Attrition (van Rooij et al, 2017. While the other eight studies (Fernández et al, 2017;Holt, 2014;Lau et al, 2018;Morton et al, 2013;Nightingale et al, 2013;Park et al, 2011;Rahat & ˙Ilhan, 2016;Ranney & Troop-Gordon, 2012) did not explicitly state the application of a particular theoretical framework to their study.…”
Section: Overview Of College Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…American scientists believe that for most students adaptation in higher education institution is stressful experience, maladjustment is common among students with avoidant behavior and coping strategy (Dyson & Renk, 2006). Daniels, Davids, and Roman (2018) believe that successful socialpsychological adaptation is the basis for further successful education, mental health and students' wellbeing. According to the results of the study, family plays a leading role in helping students to adapt.…”
Section: Problem Statementmentioning
confidence: 99%